BICS & CALP REVISITED: A CRITICAL APPRAISAL (SCIENCE TIME JOURNAL, 2026)
This paper makes an attempt to capture introductorily the notions of BICS (Basic Interpersonal Communication Skills) and CALP (Cognitive Academic Language Proficiency) introduced by Cummins. Assuming that BICS encompass rudimentary knowledge of speech and basic fluency, CALP, in contrast, evokes a high degree of cognition needed for academic subjects and tasks. In length, otheraspects of the Model termed CUP/CULP (Common Underlying Proficiency) as well as the Iceberg Model connected to the above notions are discussed. Later the paper compares the Model with Language Immersion Program to bear the Model out. Then by introducing the Threshold Hypothesis as well as the Unitary Trait Hypothesis, the study tries to relate these perspectives to the concepts of BICS and CALP.